Genome-wide identification and analysis of the NLR gene family in Medicago ruthenica - Chunyan Tong; Chunyan Tong; Yutong Zhang; Yutong Zhang; Fengling Shi; Fengling Shi (Frontiers in Genetics, 2023)
Medicago ruthenica, important forage in the legume family, possesses high nutritional value and carries abundant tolerance genes. This study used whole-genome data of M. ruthenica to perform a genome-wide analysis of the nucleotide-binding site-leucine-rich repeat receptor (NLR) gene family, which is the largest family of plant disease resistance genes (R genes). A total of 338 NLR genes were identified in the M. ruthenica genome, including 160 typical genes that contained 80 coiled-coil (CC)-NBS-LRR (CNL) genes, 76 toll/interleukin-1 receptor (TIR)-NBS-LRR (TNL) genes, four resistance to powdery mildew 8 (RPW8)-NBS-LRR (RNL) subclass genes, and 178 atypical NLR genes encoding proteins without at least one important domain. Among its eight chromosomes, M. ruthenica chromosomes 3 and 8 contained most of the NLR genes. More than 40% of all NLR genes were located on these two chromosomes, mainly in multigene clusters. The NLR proteins of M. ruthenica had six highly conserved motifs: P-loop, GLPL, RNBS-D, kinase-2, RNBS-C, and MHDV. Phylogenetic analysis revealed that the NLR genes of M. ruthenica formed three deeply separated clades according to the N-terminal domain of the proteins encoded by these genes. Gene duplication and syntenic analysis suggested four gene duplication types in the NLR genes of M. ruthenica, namely, tandem, proximal, dispersed, and segmental duplicates, which involved 189, 49, 59, and 41 genes, respectively. A total of 41 segmental duplication genes formed 23 NLR gene pairs located on syntenic chromosomal blocks mainly between chromosomes 6 and 7. In addition, syntenic analysis between M. truncatula and M. ruthenica revealed 193 gene pairs located on syntenic chromosomal blocks of the two species. The expression analysis of M. ruthenica NLR genes showed that 303 (89.6%) of the NLR genes were expressed in different varieties. Overall, this study described the full NLR profile of the M. ruthenica genome to provide an important resource for mining disease-resistant genes and disease-resistant breeding.